Effect of Leaf Guava Extract on Blood Pressure in Rattus Norwegicus Wistar Strain - Novian Swasono Hadi; Agus Wijayanarka; Ayu Bulan Febry Kurnia Dewi; Nuryani Nuryani; Misrawatie Goi (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Guava leaf extract (Psidium guajava) is a component of traditional medicine containing flavonoids, tannins, triterpenoids, and carotenoids. The study aimed to determined effect of guava leaf extract on blood pressure status of white wistar rats were given an atherogenic diet. The study method was a study experimental with design completely randomized (CRD). The group intervention was given guava leaf extract to white rats which consisted of 3 treatment levels with 5 replications namely control (P0), atherogenic diet (P1), and atherogenic diet with guava leaf extract (P2). The research phase includes the acclimatization stage for 3 days, the atherogenic diet for 2 weeks, and the intervention stage for giving guava leaf extract for 4 weeks. Data analysis used the Shapiro Walk, Kruskall-Wallis test as an alternative of One Way Anova and the Wilcoxon test as an alternative of sample t-test with a value of = 0,01. The results showed that giving an atherogenic diet affected increasing blood pressure. There was a change in blood pressure after the intervention, P0 pre-test 80,40±3,65 mmHg and post-test 83,40±2,30 mmHg (p-value= 0,197), P1 pre-test 82,80±2,59 mmHg and post-test 188,60±2,19 mmHg, (p-value = 0,042), P2 pre-test 82,80±2,17 mmHg and post-test = 108,00±2,74 mmHg (p-value = 0,042). In conclusion, giving an atherogenic diet has an effect on increasing blood pressure and giving guava leaf extract can reduce blood pressure in white wistar rats.